Campo de Dirac para fermiones sin masa - Huamaní Chaviguri, Jhonny R. (2010)
The Dirac field of massless fermions is analyzed. Considering chiral transformations in Dirac field we obtain uncoupled wave functions in which making the mass particle null a field describing the massless fermions is obtained.